2015
DOI: 10.1016/j.ijcha.2015.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Novel linkage of LMNA Single Nucleotide Polymorphism with Dilated Cardiomyopathy in an Indian case study

Abstract: BackgroundDilated Cardiomyopathy (DCM) is one of the most commonly encountered heart diseases reported globally. It is characterized by enlarged ventricles with impaired systolic and diastolic functions. Mutations in LMNA gene are one of the causative factors to precipitate the disease. However, association of SNPs of LMNA with DCM in particular has not been well documented.MethodHere we present a limited and restricted case study of patients from south eastern part of India afflicted with idiopathic DCM and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…In rs505058 SNP, an alteration from thymine to cytosine in the 3rd base of codon 446 results in a nonsense variation to Aspartic acid at exon 7 of the LMNA gene (26,27). Banerjee et al reported the linkage between rs505058 SNP of the region encoding the central rod domain of lamin A/C proteins in an Indian population in 2015 (14). Sylvius et al evaluated the relationship between two distinct LMNA mutations with cellular alterations (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In rs505058 SNP, an alteration from thymine to cytosine in the 3rd base of codon 446 results in a nonsense variation to Aspartic acid at exon 7 of the LMNA gene (26,27). Banerjee et al reported the linkage between rs505058 SNP of the region encoding the central rod domain of lamin A/C proteins in an Indian population in 2015 (14). Sylvius et al evaluated the relationship between two distinct LMNA mutations with cellular alterations (20).…”
Section: Discussionmentioning
confidence: 99%
“…Rs505058 polymorphism is an alteration in the Lamin gene's third organic base of the 446th codon located on exon seven, by which a cytosine base substitutes thymine. This single nucleotide polymorphism (SNP) is one of the most common mutations seen in familial DCM (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…Dhandapandy et al [5] described a deletion of 25 base pairs (bp) in the gene encoding cardiac myosin binding protein C (MYBPC3) is associated with heritable cardiomyopathies and increased risk of heart failure in Indian populations, with prevalence as high as ∼4%. Subsequently Indian studies were mostly limited to case reports [6] , [7] , [8] , and study of single gene in a series of patients [9] , [10] . A large study on mitochondrial DNA analysis in Indian patients with DCM revealed 48 novel, 42 disease associated and 97 private variants [11] .…”
Section: Introductionmentioning
confidence: 99%